FAKTOR YANG BERHUBUNGAN ANTARA PERSEPSI PASIEN DENGAN PERILAKU CARING DALAM PELAYANAN PERAWAT DI RUMAH SAKIT HAJI KOTA MAKASSAR TAHUN 2019 - Hanafi Kadir; Rahma Sri Susanti; Suriati Suriati (Jurnal Komunitas Kesehatan Masyarakat, 2020)
Caring behavior can affect the quality of health services and patient satisfaction in hospital, and be a determinant of the image of health care institution. This study aims to determine the relationship of education, length of treatment, level of dependence of respondents, economic condition between perception of patient with caring behavior in nursing service. This study uses analytical survey research methods, using the Cross Sectional approach. Samples that taken were 88 respondents through Purposive Random Sampling. Data collection is done through observations, interviews, documentation. Data were analyzed with the SPSS program by testing the statistical Chis-Square test for Bivariate analysis. The results showed that education (calculated X² (9,852) or P value (0,003) )< α (0,05),, length of treatment (value of X² (7,481)) or P value (0,009) )< α (0,05),, Level of dependence of Respondents (value of X² (6,168) or value of P ( 0.01) )< α (0,05),, the economic condition of X² value (8.336) or P value (0.004) )< α (0,05), means that there is a relationship between the patient's perception and caring behavior. Conclusion: There is a relationship of education, length of treatment, level of dependence of patients, and economic conditions between perceptions of patients with caring patterns in nursing services